Possible Animal Embryos from the Lower Cambrian (Stage 3) Shuijingtuo Formation, Hubei Province, South China. (March 2014) - Broce, Jesse; Schiffbauer, James D.; Sharma, Kriti Sen; Wang, Ge; Xiao, Shuhai
Abstract : Fossilized animal embryos from lower Cambrian rocks provide a rare opportunity to study the ontogeny and developmental biology of early animals during the Cambrian explosion. This paper reports possible animal embryos, along with sponge spicules, hyolithelminths, and linguliformean brachiopods, from the upper Shuijingtuo Formation limestone (Cambrian Stage 3) at Changyang, Hubei Province, South China. This limestone unit has carbonate carbon and oxygen isotopic compositions similar to the upper Shuijingtuo limestone in the Yangtze Gorges area. The Shuijingtuo embryo fossils were exposed by physical fracturing, extracted with acetic acid maceration, and observed in thin sections. They were examined using light microscopy, scanning electron microscopy, energy dispersive X-ray spectroscopic elemental mapping, and micro-focus X-ray computed tomography. Most of them are poorly preserved, with a phosphatic envelope (interpreted as a chorion or fertilization envelope) surrounding sparitic calcite. In some specimens, a polygonal pattern is present on the surface, and these are interpreted as multicelled blastula embryos. In others, sets of grooves are present on the surface of a calcitic spheroidal structure, presumably representing the calcitic interior within the chorion; these grooves are superficially similar to annulations of Markuelia embryos, but their biological significance is unknown. Although their phylogenetic and taxonomic placement is largely unconstrained, the Shuijingtuo animal embryos indicate that chorions are taphonomically more robust and are selectively phosphatized. Embryos within the chorions, on the other hand, can be completely lost or entirely replaced by calcite, with only poorly preserved surficial structures. This style of preservation can be explained by a taphonomic switch from early phosphatization to later calcitization. This study illustrates the importance of combining physical fracturing with widely used acid digestion methods in the study of calcitized animal embryos, and it alludes to the possibility that many empty phosphatic vesicles recovered by acid digestion from Cambrian carbonates may be fossilized chorions.